2021
DOI: 10.3389/fenvs.2021.769852
|View full text |Cite
|
Sign up to set email alerts
|

CALIPSO Aerosol-Typing Scheme Misclassified Stratospheric Fire Smoke: Case Study From the 2019 Siberian Wildfire Season

Abstract: In August 2019, a 4-km thick wildfire smoke layer was observed in the lower stratosphere over Leipzig, Germany, with a ground-based multiwavelength Raman lidar. The smoke was identified by the smoke-specific spectral dependence of the extinction-to-backscatter ratio (lidar ratio) measured with the Raman lidar. The spaceborne CALIPSO (Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation) lidar CALIOP (Cloud–Aerosol Lidar with Orthogonal Polarization) detected the smoke and classified it as sulfate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 54 publications
1
14
1
Order By: Relevance
“…The findings reported here contradict previous claims that the aerosol blanket that formed in the high Arctic following the Raikoke eruption was composed almost entirely of smoke particles (Ansmann et al, 2021;Ohneiser et al, 2021). It was not clear what caused the aerosol misclassification from the ground-based results.…”
Section: Discussioncontrasting
confidence: 93%
“…The findings reported here contradict previous claims that the aerosol blanket that formed in the high Arctic following the Raikoke eruption was composed almost entirely of smoke particles (Ansmann et al, 2021;Ohneiser et al, 2021). It was not clear what caused the aerosol misclassification from the ground-based results.…”
Section: Discussioncontrasting
confidence: 93%
“…Rather low depolarization ratio values were found at all after the beginning of the MOSAiC campaign in October 2019 (about 80 days after injection into the UTLS height range over Siberia). Lidar measurements of stratospheric smoke layers over Leipzig, Germany, in August 2019 (originating from the SILBE fires according to backward trajectory analysis) and with CALIOP also revealed low smoke depolarization ratios (Ansmann et al, 2021b). This strong contrast to the ANYSO and PNE depolarization features again points to the fact that different lifting processes took place.…”
Section: Smoke Intensive Parametersmentioning
confidence: 92%
“…The multiwavelength polarization Raman lidar techniques as applied at Punta Arenas is used for tropospheric wildfire smoke characterization since more than 20 years (Wandinger et al, 2002;Müller et al, 2005). We expanded the range of applications towards stratospheric smoke after the record-breaking Canadian fires in August 2017 (Haarig et al, 2018), the huge Siberian fires in July-August 2019 (Ohneiser et al, 2021), and the Australian fires (Ohneiser et al, 2020;Ansmann et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Omar et al (2009) [40] indicated that a maximum uncertainty of 30% is associated with the determination of lidar ratios. A significant underestimate of aerosol extinction in clean regions is also possible [42], while CALIOP could also misclassify low aerosol concentrations as clear air when no aerosol is detected due to the CALIOP detection threshold. A recent study [43] also showed a misclassification between smoke and sulphate aerosol layers.…”
Section: The Cloud-aerosol Lidar and Infrared Pathfinder Satellite Ob...mentioning
confidence: 99%
“…A horizontal averaging of 105 km was applied to the CALIOP data to enhance the detection of the aerosol layers and increase the signal-to-noise ratio of the profiles. The data were screened using standard CALIPSO quality-assurance flags and cloud aerosol discrimination (CAD) scores [39,42]. At this point, it is worth mentioning that, since September 2016, CALIOP has been experiencing low-laser-energy shots, which mostly occur over the South Atlantic Anomaly (SAA) region.…”
Section: The Cloud-aerosol Lidar and Infrared Pathfinder Satellite Ob...mentioning
confidence: 99%